Recent Advances in the Synthesis of Pyrazole Derivatives Using Multicomponent Reactions - Maddila, Suresh; Jonnalagadda, Sreekantha B.; Gangu, Kranthi K.; Maddila, Surya N. (Current Organic Synthesis, 2017)
Aim and Objective: In this review, we summarize the current state of varied multicomponent/onepot protocols for synthesis of vital pyrazole derivatives under varied conditions, including in absence and presence of catalysts, solvent and solvent-free conditions, and using other techniques such as microwave irradiation and ultrasonication. In broad sense, this review covers the publications up to 2015. Material and Method: All the pyrazole derivatives were synthesized by using various techniques such as ultrasonication, heterogeneous catalysts, microwave irradiation and homogeneous catalyst systems. Results: As convincingly demonstrated by the synthetic approaches reported in this review, MCRs have facilitated many new methodologies with significant advantages for efficient and well organized synthesis of varied pyrazole derivatives. The methodology involved variety of options for catalysts that can be chosen using different solvents or solvent-free conditions and/or using alternative energy-efficient options such as microwave irradiation and sonification. This review brings together ample material about synthesis of varied pyrazole derivatives that may have prodigious scope, in drug design and therapeutics. It is anticipated that research efforts in this direction will endure in the search for novel, atom efficient, small molecules with excellent drug-like properties. Conclusion: As convincingly demonstrated over a selection of studies reported in this review, the uses of MCRs have facilitated many new methodologies with significant advantages for efficient and well organized synthesis of varied pyrazole derivatives. The diversity in approach, variation in transformations and scope of modification of pyrazoles were holistically summarized in this review.
Keywords: green chemistry